The Role of the Madrasah Principal's Supervision in Enhancing the Performance Quality of School Administrative Personnel - Fahra, Suhada Aulia; Syukri, Makmur (Thawalib: Jurnal Kependidikan Islam, 2025)
The supervision of the madrasah principal plays a vital role in guiding and developing administrative staff to work optimally through coaching, evaluation, and human resource empowerment approaches within the madrasah administrative environment. This study aims to analyse the influence of the principal’s supervision on the quality of administrative staff performance and to identify problems and solutions for improving administrative performance. The research employs a qualitative case study approach. Data were collected through interviews, observations, and documentation, and were analysed using data condensation, data display, and conclusion drawing. The findings reveal that the principal supervises through annual planning, direct observation, two-way communication, and regular evaluations. The supervision includes aspects of discipline, service, and the use of technology. Evaluations are carried out through meetings and feedback, followed by training, task restructuring, and mentoring. This participatory approach encourages performance improvement and fosters a reflective and adaptive work culture within the madrasah administrative environment. The principal’s supervision creates a more orderly, professional, and collaborative work environment. Administrative staff become more disciplined, productive, receptive to feedback, and adaptable to changes and technology. Conclusion: The principal’s supervision contributes significantly to improving the performance of administrative staff through observation, evaluation, coaching, training, and a participatory and communicative approach that fosters a conducive work atmosphere.